P-176 I want to die alone nurse, i want to die at home. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Carpenter, Jane
Abstract : Supporting a patient with limited family and financial resource to die alone at home, when some people were profoundly uncomfortable with their end of life wishes proved a difficult, but not insurmountable, challenge. Background: The concept of a 'Good Death' (Ko et al., 2015) is widely accepted, dying alone is seen as an aspect of 'bad death'. The Mental Capacity Act (2005) makes it clear, people have a right to make informed choices; these choices should not be measured against those others might make. Patients who want to die alone are not always able to do so – well-meaning friends, neighbours and professionals can create barriers to prevent lone death including detailing safety, medicines and vulnerable adult concerns. Results: The patient died at home, alone, what did we do ? Enabled the patient to be explicit about their choices, and communicate them to friends, neighbours and professionals effectively Recognised that dying alone was a valid choice, made with capacity, and fully in tune with the context of this person's life Reflected on our insecurities, helped carers to do the same, recognising that our fear can create a barrier to patient choice Brought together the widest multidisciplinary team including social services, carers, neighbours, helping them to understand the patient's viewpoint, right to autonomy and self-determination Honestly addressed risks to patient safety, safeguarding, medicines management, access to patient's home – minimising those risks using technology, equipment adaptations and creative problem solving Rapid response hospice team involved. Conclusions: The biggest challenge was to overcome preconceptions of what is a good death to enable the patient to have their choices honoured. Creating common understanding with good communication, having a clear plan, and taking a degree of shared risk empowered real patient choice at end of life. An alone death is not necessarily a bad death.